Characterization of existing artisanal fisheries in Fernando de Noronha/PE, Brazil: - Campos Zeineddine, Gabriela (2024)
This work aimed to describe the categories of fishing carried out in Fernando de Noronha, which subsidize fishing planning, contribute to the conservation of associated biodiversity and valorization of traditional fishing activity. Data were collected through interviews carried out within the scope of fishing monitoring, and in participatory diagnosis meetings with the fishing community and managers. For a better understanding and characterization of the activity, during these diagnostic meetings, a timeline was constructed with the main changes related to island artisanal fishing. There are currently an average of 94 fishermen in Fernando de Noronha, of which 35 fish from beaches and 59 from boats. The fishing fleet is made up of 46 vessels, but only 19 are exclusively for fishing. According to the fisheries law, local fishing activity falls into four categories of fishing: professional, subsistence, amateur and scientific. Subsistence and professional fishing occur more frequently, however amateur fishing has been growing exponentially, through fishing tourism, an activity that forms an interface between professional and amateur fishing and, as it is a relatively new activity, is in a opportune scenario for ordering. This work characterized the types of fishing activity existing in Fernando de Noronha. According to the perception of changes and increase in amateur fishing (fishing tourism), it is suggested that this activity be organized in a particular way, with specific rules aimed at conserving the explored natural resources, in addition to the cultural and economic values ​​of the community.